Emma Corwin: capstone - Corwin, Emma, artist (Colorado State University. Libraries, 2021)
The artist's statement: I am a creative. As a child, I would fill an entire page with tiny scribble-marks in every color, going every direction. I would wear striped tights with a scarf tied around my waste with my head held high. I've sold t-shirts and stationary with my wonky little imaginings. I am inspired by the unconventional and approach challenges with an interesting eye. Graphic design has become my outlet for expression. I have always sought unique avenues to use my passion, my talents and my voice for the betterment of my community. Currently, I design for the Women and Gender Advocacy Center at CSU; an office that supports assault survivors. I have also done graphic design work for the Milwaukee Tennis and Education Foundation, and I have volunteered with the Black Lives Matter mural project on the Colorado State University campus. Creating socially conscious design is my top priority. My process often begins off screen. I sketch and ideate. I journal and research. Considering all viewers and inclusivity is important in my design. I often give hierarchy to imagery, with my primary goal being to pull the viewers in so the information becomes relevant. Some of my favorite work has been my hand drawn illustrations, including the book I wrote and illustrated, titled, "Sentiments and Small Interruptions." Keeping the artists hand in my work has remained important to what I produce. I treat my designs as a fine artist approaches a canvas. They are not mechanical, they are touched, and cared for. But just as important as they are as works of art, my designs are clean and professional.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design